Effects of smoking bans on passive smoking exposure at work and at home. The European Community respiratory health survey. (26th April 2019) - Olivieri, Mario; Murgia, Nicola; Carsin, Anne‐Elie; Heinrich, Joachim; Benke, Geza; Bono, Roberto; Corsico, Angelo Guido; Demoly, Pascal; Forsberg, Bertil; Gislason, Thorarinn; Janson, Christer; Jõgi, Rain; et al.
Abstract: This longitudinal study investigated whether smoking bans influence passive smoking at work and/or at home in the same subjects. Passive smoking at work and/or at home was investigated in random population samples (European Community Respiratory Health Survey) in 1990‐1995, with follow‐up interviews in 1998‐2003 and 2010‐2014. National smoking bans were classified as partial (restricted to public workplaces) or global (extended to private workplaces). Multivariable analysis was accomplished by three‐level logistic regression models, where level‐1, level‐2, and level‐3 units were, respectively, questionnaire responses, subjects, and centers. Passive smoking at work was reported by 31.9% in 1990‐1995, 17.5% in 1998‐2003, and 2.5% in 2010‐2014. Concurrently, passive smoking at home decreased from 28.9% to 18.2% and 8.8%. When controlling for sex, age, education, smoking status, and ECHRS wave, the odds of passive smoking at work was markedly reduced after global smoking bans (OR = 0.45, 95% CI 0.25‐0.81), particularly among non‐smokers, while the protective effect of global smoking bans on passive smoking at home was only detected in non‐smokers. Smoking bans both in public and private workplaces were effective in reducing passive smoking at work in Europe. However, given the inefficacy of smoking bans in current smokers' dwellings, better strategies are needed to avoid smoking indoors.